2010
DOI: 10.1371/journal.pone.0008678
|View full text |Cite
|
Sign up to set email alerts
|

Two Regulators of Vibrio parahaemolyticus Play Important Roles in Enterotoxicity by Controlling the Expression of Genes in the Vp-PAI Region

Abstract: Vibrio parahaemolyticus is an important pathogen causing food-borne disease worldwide. An 80-kb pathogenicity island (Vp-PAI), which contains two tdh (thermostable direct hemolysin) genes and a set of genes for the type III secretion system (T3SS2), is closely related to the pathogenicity of this bacterium. However, the regulatory mechanisms of Vp-PAI's gene expression are poorly understood. Here we report that two novel ToxR-like transcriptional regulatory proteins (VtrA and VtrB) regulate the expression of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
78
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 49 publications
3
78
0
Order By: Relevance
“…Similar conclusions were drawn for the homologous T3SS regulatory proteins in Vibrio parahaemolyticus, VtrA and VtrB, based on data from complementation and electrophoretic mobility shift assays (36,37). Interestingly, when the V. cholerae ⌬vttR A strain was complemented by using vttR B , we observed cytotoxicity using a lower arabinose concentration than that for complementation with pBAD18-vttR A (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…Similar conclusions were drawn for the homologous T3SS regulatory proteins in Vibrio parahaemolyticus, VtrA and VtrB, based on data from complementation and electrophoretic mobility shift assays (36,37). Interestingly, when the V. cholerae ⌬vttR A strain was complemented by using vttR B , we observed cytotoxicity using a lower arabinose concentration than that for complementation with pBAD18-vttR A (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…Nevertheless, it has also been shown that mutant strains lacking tdhS and tdhA genes are still able to cause intestinal fluid accumulation in the same model (26). There is also evidence indicating that T3SS2 is an important factor in fluid secretion for ileal-loop models (17,18,27). In the present study, the clinical signs of infected piglets resembled the gastrointestinal presentation of the human disease.…”
Section: Discussionsupporting
confidence: 56%
“…Nevertheless, because T3SS2 is encoded by genes carried on an 80-kbp pathogenicity island and the genes encoding T3SS2 are flanked by tdhA and tdhS in the pandemic serovar (17), it is possible that the mutation of a T3SS2 structural gene could have polar effects on the synthesis of TDH. This possibility is enhanced on the basis of the fact that we have been unable to complement either of our T3SS1 or T3SS2 deletion mutant strains, probably owing to polar effects within the islands carrying the genes encoding the T3SSs.…”
Section: Discussionmentioning
confidence: 99%
“…Vibrio parahaemolyticus contains a ToxRS homologue, but the role ToxRS plays in the pathogenicity of this organism has not been fully elucidated (38,67,68). Data suggesting that ToxRS is involved in regulating TDH expression (38) have been confounded by evidence suggesting that two ToxR-like regulators, vtrA and vtrB (located within VPaI-7), control the levels of TDH expressed in V. parahaemolyticus (33).…”
mentioning
confidence: 99%